Enacting the IS Strategy: Transforming a Strategic Actor Vision into Praxis - Bohórquez López, Victor Wilfredo (2012)
In the education sector, online knowledge sharing and online social learning are fundamental in the new education landscape. But some years ago, in some prestigious education institutions, talking about online education and online communities was like a taboo. The focus of this research study is an academic and international institution, where a visionary ahead of his time saw the importance of online social networks before the boom they experienced. With this idea in mind, he proposed to create an online knowledge community platform (OKCP). We describe the OKCP different development stages paying special attention to the most important events that shaped and motivated the (re)creation of this environment. In this sense, the main contribution of this study is to make us reflect on how the strategy-as-practice approach is useful for a better understanding of the evolutionary process of an IT-based innovation product (OKCP), describing how the different streams of strategies and praxes (re)shape the intrinsic characteristics of the product, transforming it gradually into what actors want it to be.